A Concept of Philosophy in the Qur'anic Context - Alparslan Acikgenc (International Institute of Islamic Thought, 1994)
One of the most debated subjects in philosophy is the nature and subject matter of philosophy itself. It is pethaps the only discipline that critically discusses its own natum. This is one msan that has led philosophers, particularly after the nineteenth century, to distinguish philosophy from such other experimental sciences as physics, biology, or astronomy. When we add to this the nature of subjects discussed in philosophy, as opposed to the issues discussed in those sciences, the sharp distinction between the two becomes decisively clear. It is our aim to investigate critically the nature of philosophical subjects, which constitub basically the method of philosophy, in order to arrive at a concept of philosophy that is acceptable to the Qur'anic perspective, which can be taken, as we shall see, as a contribution toward the effort of Islamization. Our discussion requim the development of a clear conception of the term "philosophy." If we am to develop an Islamic concept of philosophy, then we are required in the first instance to clarify what we mean by philosophy. We feel compelled to do this, because in the history of human thought thew am more than a score of conceptions about the nature, purpose, and subject matter of philosophy. However, settling this problem alone does not fulfill the task of our paper. We must, moreover, show what the role of philosophy may be in this society (in general) so that we can delineate mow effectively its significance in a Muslim community (in particular). Finally, we must try to justify our arguments from the Qur'anic perspective in order to defend the conception of philosophy that is to be developed hew as an adequate one. The discussion, then, will be divided into three main sections. The first section will be devoted to "what philosophy is." In the second, we shall elucidate what we shall tern the "Qur'anic conception of or attitude ...